Bioindicators of Behavior and Regeneration of a Caatinga Area in the Brazilian Semi-Arid - A Review - da Costa, Cassio Ricardo Goncalves; Silva, Marcos Gomes da; da Costa, Carlos Antonio Gonçalves; da Cunha, Rayane Sley Melo; de Sousa, Marcia Mayara; de Sousa, Maria Vanessa Pires; Maia Linhares, Anne Carolline; Silva, Sonaria de Sousa; Marques, Ailson de Lima; Moura, Debora Coelho de (Journal of Forests, 2022)
Studies that allow the understanding of the nutrient cycling processes and maintenance of soil fertility in the caatinga biome are necessary to assist in the proposal of possible management forms, in view of the sustainability of this ecosystem, to provide data in an area of knowledge the quantification of glomalin can be a good indicator of changes caused by the use of the soil and, in turn, therefore, it can become a good indicator of its recovery because it is correlated with important attributes of the soil. In addition to providing data of this process for a better understanding of the soils of the country, a study on this subject will also contribute with a new database for global monitoring. Research that can follow the regeneration rate of Caatinga forests in the Semi-arid will allow the development of models relating to several variables, not currently available for the semi-arid tropical region.